IMPLEMENTASI PENGUATAN KARAKTER PROFESIONAL CALON GURU MELALUI ASISTENSI MENGAJAR DI UPT SDN 060971 MEDAN TUNTUNGAN: Penelitian Tindakan Kelas - Darinda Sofia Tanjung, Grace Elisabet Mahulae, Pasya Pebina Pandia; Marcella Sirait, Saur Tua Lumban Gaol, Jhon Rapindo Sipayung (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Teaching assistance activities are a strategic program to strengthen the professional character of prospective teachers by providing real teaching experience in the educational field. The problem highlighted in this study is the need to enhance the teaching skills of student teachers through direct experience in elementary schools. This study aims to explore how the implementation of teaching assistance contributes to shaping students’ professional character within the context of school-based learning. The research employed a guided practice method, where student teachers conducted various teaching-related activities at UPT SDN 060971 Medan Tuntungan. These included academic instruction, non-academic activities, integration of technology in learning, classroom management, and participation in administrative tasks. The findings revealed that the program positively impacted students' competencies in managing learning processes, engaging with pupils, and addressing challenges in real classroom settings. It can be concluded that teaching assistance serves as an effective medium for fostering the professional character of student teachers, encompassing pedagogical, social, and managerial aspects.